Fitoquímica e atividades antirradicalar, fotoprotetora e antibacteriana de Ruellia angustiflora (Nees) Lindau ex Rambo - Zadra, Marina (2023)
The use of plants for their medicinal properties is as old as mankind itself. Ruellia angustiflora (Acanthaceae) is a species popularly known as “fire flower” and used in traditional medicine as a wound healing agent. However, few studies are found in the literature about its chemical composition and biological activities. Thus, this work aimed to carry out a phytochemical study and determine the antiradical, photoprotective and antibacterial activities of the root (Ra-R), stem (Ra-C) and leaves (Ra-F) of this species. The extractions (0.2%; 1% and 5%) were carried out in an ultrasound bath and 95% ethanol as solvent, and the process was monitored to determine the ideal time, for 5 hours. The content of total phenolic compounds, flavonoids and tannins was determined, and the characterization of the extracts was performed by HPLC-UV. The antiradical activity was determined by the DPPH method, the in vitro photoprotective activity was evaluated by spectrophotometry and the antibacterial activity was performed by the agar perforation method. Extraction rates were more pronounced in the first minutes, but after 60 minutes they remained practically stable. Thus, 60 minutes was considered the ideal extraction time, aiming at optimizing the process. The solid/liquid ratio was also an analyzed parameter, and according to the extraction efficiency, yield and cost-effectiveness, 1% extracts (m/v) were prioritized for additional tests. In the phytochemical analysis, Ra-R showed the highest amount of phenolic compounds, and Ra-F showed the highest amount of flavonoids. Condensed tannins were not identified in the extracts. The kinetics of the DPPH reaction with the extracts showed a biphasic behavior, with a rapid decay of the radical concentration in the first minutes, followed by a slow step. Ra-R and Ra-F showed similar IC50 values, while Ra-C showed higher values, which is probably due to its lower content of total phenolic compounds. Five phenolic compounds were identified in the extracts: caffeic acid, ferulic acid (main peak), rutin, quercetin and luteolin. Through the DPPH-HPLC screening, it was observed that ferulic acid, rutin and quercetin are mainly responsible for the antiradical activity of the extracts. The extracts showed significant absorption in the UV region of the spectrum and relevant photoprotective activity, especially Ra-F (SPF = 23), possibly due to its high content of flavonoids. The antibacterial activity of the extracts was also verified against Gram-positive bacteria Staphylococcus aureus and Streptococcus pyogenes, species frequently associated with skin infections, and Ra-R showed a halo of inhibition similar to erythromycin on S. pyogenes. The extracts were inactive against Gram-negative bacteria by the method used. Together, these data reveal the potential of Ruellia angustiflora as an active ingredient for the development of multifunctional formulations.